Comparative Study of Clinical And Metabolic Parameters in Type 2 Diabetes Mellitus Patients Consuming Germinated Brown Rice Versus White Rice - Noor Amiza Binti Zainal Abidin (Universiti Sains Islam Malaysia, 2024)
Matric: 3182468 (FPSK)